Complications of Thyroid Surgery and their risk factors in Malignant Thyroid disease: A Retrospective Study at a Tertiary Care Cancer Center of Nepal - Shrestha, Kumar; Gautam, Dej Kumar; Karki, Anil Bikram; Karmacharya, Dilip; Shrestha, Amar; Adhikari, Sandichhya; Neupane, Bijay (Nepalese Journal of Cancer, 2026)
Background: For the last few decades, the increase in the incidence of thyroid diseases including malignancies resulted in the increase in the number of thyroid surgeries as well. Thyroidectomy represents one of the commonest surgery performed by otolaryngologists. Thyroidectomy has potential complications like Hematoma, wound infections, hypocalcemia, hoarseness etc. These surgery related complications depends on the type and severity of disease, lack of identification of Recurrent Laryngeal Nerve and parathyroid glands, extent of surgery, neck dissection, previous surgery and size of tumor.Aims: The aim of this study is to evaluate the complications of thyroid surgery for malignant thyroid disease and to analyze the risk factors of the complications.Methods: A retrospective study was done from August 2024 to July 2025 in 153 patients with malignant thyroid disease who underwent surgical treatment in ENT-Head and Neck Oncosurgery unit, BP Koirala Memorial Cancer Hospital by reviewing the medical records of all these patients. The postoperative complications and the risk factors associated with these complications were evaluated.Results: Out of 153 patients with malignant thyroid disease, total thyroidectomy was done in 103 (67.3%) patients, hemithyroidectomy in 33 (21.6%) patients and completion thyroidectomy in 17 (11.1%) patients. 62 (40.5%) patients develop complications after thyroid surgery. Most common complication was hypocalcemia alone in 39 (25.5%) followed by recurrent laryngeal nerve (RLN) palsy alone 5 (3.3%), hematoma 3 (2%), Chyle leak alone 3 (2%), hypocalcemia with chyle leak in 6 (3.9%) & hypocalcemia with hoarseness in 3 (2%). Other less common complications were tracheal injury, oesophageal injury & injury to right pyriform sinus (PFS) & pre-vertebral muscles.Conclusion: Hypocalcaemia was the most frequent post-thyroidectomy complication, while voice change, hematoma, chyle leak are additional complications. Surgeons have to pay attention to curtail the complications during thyroid surgery.